The Chronology of Palestine in the Early Second Millennium B. C. E - Weinstein, James M. (Bulletin of ASOR, 1992)
Four major chronological schemes-the ultra-high, high, middle, and low-exist for the early second millennium B. C. E. in Palestine. Those schemes differ primarily in their dating of the MB IIA and transitional MB IIA/B periods. The evidence adduced for the chronology of those periods comes from the excavations at Tell el-Dabʿa in Egypt's eastern Delta, and Egyptian objects (especially scarabs) found at various sites in the Levant. An analysis of the archaeological and historical data indicates that the MB IIA period began in the early 19th century B. C. E., while the transition from MB IIA to MB IIB probably occurred during the latter years of the 18th century B. C. E. The middle and low chronologies are both possible based on the current evidence for the MB IIA/B transition.